2004
DOI: 10.1386/ijtm.3.1.3/0
|View full text |Cite
|
Sign up to set email alerts
|

The implications of privatization for innovation in Brazilian telecommunications

Abstract: This article discusses the key role played by the Brazilian telecommunications sector throughout the 1970s and 1980s in building and consolidating a sectoral innovation system (SIS) as part and parcel of a strategy to unify the existing network. The sector provided the essential conditions for the formation of a national technological capability, as was shown by the establishment of the Research and Development Centre of Telebrás (CPqD). A new debate arose, however, which led to the privatization of the Teleb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It has also resulted in huge foreign direct investments (FDI) inflows into the gold mining sector and resultant influx of Western multinationals into the sector. The present state of ownership of gold mining companies in Ghana indicates this 'subsidiarity' control of vast mining concessions (Shima, 2004;Dansereau, 2005). Recently Eshun and Jellicoe (2011) revealed that not a single gold mining company is wholly owned by the government of Ghana and/or Ghanaian investors.…”
Section: Introductionmentioning
confidence: 99%
“…It has also resulted in huge foreign direct investments (FDI) inflows into the gold mining sector and resultant influx of Western multinationals into the sector. The present state of ownership of gold mining companies in Ghana indicates this 'subsidiarity' control of vast mining concessions (Shima, 2004;Dansereau, 2005). Recently Eshun and Jellicoe (2011) revealed that not a single gold mining company is wholly owned by the government of Ghana and/or Ghanaian investors.…”
Section: Introductionmentioning
confidence: 99%
“…• Privatization leads to more commercially oriented R&D and innovation (Belloc, 2014;Shima, 2004;Somé, Cano-Kollmann, Mudambi, & Cosset, Forthcoming) Internationalization • • Privatization does not lead to higher levels of internationalization (Alonso et al, 2013;Clifton et al, 2010)…”
mentioning
confidence: 99%